Nanocrystalline cellulose from microcrystalline cellulose of date palm fibers as a promising candidate for bio-nanocomposites: isolation and characterization - Hachaichi, Amina; Kouini, Benalia; Lau, Kia Kian; Asim, Mohammad; Fouad, Hassan; Jawaid, Mohammad; Sain, Mohini (MDPI, 2021)
Date palm fiber (Phoenix dactylifera L.) is a natural biopolymer rich in lignocellulosic components. Its high cellulose content lends them to the extraction of tiny particles like microcrystalline cellulose (MCC) and nanocrystalline cellulose (NCC). These cellulose-derived small size particles can be used as an alternative biomaterial in wide fields of application due to their renewability and sustainability. In the present work, NCC (A) and NCC (B) were isolated from date palm MCC at 60 min and 90 min hydrolysis times, respectively. The isolated NCC product was subjected to characterization to study their properties differences. With the hydrolysis treatment, the yields of produced NCC could be attained at between 22% and 25%. The infrared-ray functional analysis also revealed the isolated NCC possessed a highly exposed cellulose compartment with minimized lignoresidues of lignin and hemicellulose. From morphology evaluation, the nanoparticles’ size was decreased gradually from NCC (A) (7.51 nm width, 139.91 nm length) to NCC (B) (4.34 nm width, 111.51 nm length) as a result of fragmentation into cellulose fibrils. The crystallinity index was found increasing from NCC (A) to NCC (B). With 90 min hydrolysis time, NCC (B) showed the highest crystallinity index of 71% due to its great cellulose rigidity. For thermal analysis, NCC (B) also exhibited stable heat resistance, in associating with its highly crystalline cellulose structure. In conclusion, the NCC isolated from date palm MCC would be a promising biomaterial for various applications such as biomedical and food packaging applications.